Millions - Cottrell Boyce, Frank (London : Macmillan Children's Books, 2008)
The Cunningham brothers literally have money drop in their laps when a bag of cash falls from the sky; however, the crooks who initially stole the loot are hot on the trail to retrieve it.
5.7
3-6.
3-6
Keywords: Brothers -- Fiction; Conduct of life -- Fiction; Grief -- Fiction; Money -- Fiction; Saints -- Fiction; Visions -- Fiction; Brothers -- Fiction; Conduct of life -- Fiction; Grief -- Fiction; Money -- Fiction; Saints -- Fiction; Visions -- Fiction; England -- Fiction; England -- Fiction